Venezuelan Migration in Ecuador: A Look at Before and After the Pandemic - Basantes, Samantha (2025)
Since 2015, the departure of Venezuelan citizens to Latin American countries modified the migratory landscape of the region. Ecuador has turned out to be one of the main destinations, both for transit and for reception. The country has made a series of changes in its migration policies, reaching a radical modification towards 2018. Thepandemic caused by COVID-19, increases the vulnerability of Venezuelan population residing in Ecuador. Therefore, this paper studies the response of the Ecuadorian State to the Venezuelan migratory wave before and after the COVID-19 pandemic. To carry out this work, previously collected data is analyzed. These focus on areas such as economic activity, housing conditions and education of the Venezuelan population residing in Quito - Ecuador. As a result, it is found that the Ecuadorian legislation raises a series of guarantees, which in practice are not fulfilled. It is concluded that there is a need to rethink the operation of Ecuadorian institutions.